Metastatic melanoma masquerading as a furuncle - Imran Aslam; Jonathan Konopinski; Nasir Aziz (Our Dermatology Online, 2017)
Melanoma metastasizes to the skin in about 10-17% of patients. Although there are reports of metastatic melanoma masquerading as panniculitis and erysipelas, it is very uncommon for it to present as an inflammatory skin lesion. When malignant melanoma cells invade the superficial dermal lymphatic vessels it can result in erythema, edema and induration of the overlying skin. This presentation can be problematic for clinicians if they do not suspect melanoma and choose not to biopsy the lesion. We report a case of an elderly man with a history of invasive melanoma who presented with a furuncle-like lesion that was found to be in-transit metastatic melanoma.